STRENGTHENING PUBLIC SERVICE DELIVERY THROUGH DIGITAL GOVERNANCE: A COMPARATIVE ANALYSIS OF INDONESIA AND SOUTH KOREA - Khasanah Septi Aningrum, Uswatun; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
Digital governance has become a central strategy for strengthening public service delivery and improving governance quality in contemporary public administration. This article examines how digital governance reforms shape public service delivery in Indonesia and South Korea through a systematic literature review and comparative analysis. The study aims to identify similarities, differences, and transferable lessons between the two countries by synthesizing existing research on bureaucratic reform, e-government initiatives, and governance outcomes. A systematic review was conducted on peer-reviewed journal articles, policy reports, and publications from international organizations indexed in major academic databases over the last two decades. The analysis applies a thematic synthesis approach to classify findings across governance reforms, bureaucratic capacity, anti-corruption efforts, and digital public service innovation. The review shows that while both countries demonstrate strong political commitment to digitalization, South Korea has achieved more coherent and integrated outcomes due to its merit-based bureaucracy, centralized coordination, and long-term digital strategy. Indonesia, in contrast, continues to face challenges related to institutional fragmentation, uneven administrative capacity, and implementation gaps. This article contributes to comparative public administration by linking digital governance with bureaucratic performance and governance quality in two Asian democracies. It also provides context-sensitive policy implications for strengthening digital public services in developing countries.